Stefan Żeromski na łamach „Tygodnika Ilustrowanego” w roku 1912 - Gabryś-Sławińska, Monika (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The objective of the present article is to analyze Sine ira, the cycle of sketches by Adam Grzymała-Siedlecki, as a testimony of Stefan Żeromski’s impact on shaping historical and political ideas of his times, but also as the new manner the works of a known artist functioned on the pages of „Illustrated Weekly”. After having presented current reviews and publication of Żeromski’s oeuvre, in 1912 the editors of the Warsaw journal offer its readers a critical overview of The History of Sin and Rose, both inspired by the revolution of 1905-1907. The accusations unmasking the “errors” in thinking and writing about the revolution formulated by the journalist take into consideration particularly the recipient’s perspective. These accusations are becoming part of the journal’s strategy to inform about conflicts, current in the context of growing antagonisms in Europe.